2021
DOI: 10.1136/jitc-2020-000832
|View full text |Cite
|
Sign up to set email alerts
|

Skin dendritic cells in melanoma are key for successful checkpoint blockade therapy

Abstract: BackgroundImmunotherapy with checkpoint inhibitors has shown impressive results in patients with melanoma, but still many do not benefit from this line of treatment. A lack of tumor-infiltrating T cells is a common reason for therapy failure but also a loss of intratumoral dendritic cells (DCs) has been described.MethodsWe used the transgenic tg(Grm1)EPv melanoma mouse strain that develops spontaneous, slow-growing tumors to perform immunological analysis during tumor progression. With flow cytometry, the freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The increased expression of CD83 and CD40 on migratory cDC subsets in tremelimumab-treated SLN in our study was likely an indirect result of enhanced pro-inflammatory cytokine signaling and/or decreased aT reg rates at the dermal injection site. The finding that CTLA-4 blockade preferentially interferes with migratory cDC is in keeping with their higher expression levels of CD80 and CD86 ( 40 ) and their reported cross-talk with T regs during or right after their migration to skin-draining lymph nodes, which is involved in the maintenance of self-tolerance ( 53 57 ). We thus provide clinical evidence that CTLA-4–mediated interactions between migratory cDC and aT reg in TDLN (with elevated surface levels of CTLA-4) are pivotal in setting the levels of both local and systemic aT regs .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The increased expression of CD83 and CD40 on migratory cDC subsets in tremelimumab-treated SLN in our study was likely an indirect result of enhanced pro-inflammatory cytokine signaling and/or decreased aT reg rates at the dermal injection site. The finding that CTLA-4 blockade preferentially interferes with migratory cDC is in keeping with their higher expression levels of CD80 and CD86 ( 40 ) and their reported cross-talk with T regs during or right after their migration to skin-draining lymph nodes, which is involved in the maintenance of self-tolerance ( 53 57 ). We thus provide clinical evidence that CTLA-4–mediated interactions between migratory cDC and aT reg in TDLN (with elevated surface levels of CTLA-4) are pivotal in setting the levels of both local and systemic aT regs .…”
Section: Discussionmentioning
confidence: 65%
“…Others show no decrease in absolute T reg numbers in the TME by quantitative immunohistochemistry ( 48 ). Differences may in part be explained by assessment of T reg levels at different time points after CTLA-4 blockade ( 24 , 53 , 54 , 58 ). Previous studies, limited to patients with advanced or metastatic melanoma, have not reported a consistent pattern of change in peripheral blood T reg frequency after systemic anti–CTLA-4 treatment ( 59 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…These mice develop spontaneous melanoma without any chemical or UV induction; therefore we propose that the tumor-stromal interactions as well as the tumor-immune system interactions are physiologically relevant to human melanomas. This notion was supported by the report that these mice have similar immune system dysfunctions as human melanoma patients and is one of the contributors to melanoma development [111][112][113][114]. Further discussion of the immune dysfunction occurring in our Grm1driven melanoma mice have been reviewed by Eddy et al, in "Overcoming Immune Evasion in Melanoma" [1].…”
Section: Therapeutic Targeting Of Metabotropic Glutamate Receptor 1 Expressing Melanomasmentioning
confidence: 77%
“…Dendritic cells are specialized antigen-presenting cells that can effectively activate T cell immunity against SKCM [33][34][35], and are signi cantly associated with an improved survival time in SKCM patients [36]. As the key trigger of pyroptosis, the NLRP3 in ammasome activated by dying tumor cells can stimulate DCs, thus effectively priming CD8 + T cells by secreting IL-1β, and thereby inducing a strong and durable tumor immune response [37].…”
Section: Discussionmentioning
confidence: 99%